Mobilna telefonija u funkciji uklapanja u evropske prometne tokove - Markežić, Ivan (Promet - Traffic&Transportation, 2012)
The author exposes the development aspect of the mobile telephone systems in Europe and mentions the three regions of compatible systems (Scandinavia, Benelux and Great Britain with Ireland) while some special systems are operated by France and Germany. Seeing the inevitability of introduction of a common system, CEPT has formed the GSM Project i.e. a trans-European mobile telephone communication system joined by 17 European countries to be functioning from the year 1991. In the closing lines the author expresses his regrets regarding our activities on a different incompatible system - the NMT 450- so that it is po8Sible for us to meet considerable difficulties in the future in the process of integration into the trans-European GSM system.